A POST-COLONIAL HERMENEUTICAL CRITICISM OF BIBLICAL AND QUR’ANIC TEACHINGS ON WOMEN’S LEADERSHIP - Le Ngoc Bich Ly (TANGKOLEH PUTAI, 2018)
In our time, women’s rights have been significantly improved especially in politics, education, and economics. However, women have still faced strong obstacles to fully participate at the decision-making level in some religious institutions. Gender-biased religious texts are often quoted to silence and discourage women from going forward. Instead of reinterpreting the gender-biased texts as feminist scholars often do, this paper will deconstruct the process of textual production and interpretation by using the lens of feminist post-colonial hermeneutics. It does this by taking the two case studies of the Biblical and Qur’anic teachings on women’s leadership. It argues that the process of textual production and interpretation of these texts were influenced by colonialism and patriarchy of their time.